Enhancing Entrepreneurship Skills in MAN 5 Agam Students through a Studentpreneurship Program - Dedi Efendi; Ismail Md. Zain; Yuni Elfida; Adryan Syah Putra; Shobrina Shifa Auliya (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2024)
The evolving era of the Industrial Revolution 4.0 demands that individuals possess a diverse range of skills, including entrepreneurship. However, students at MAN 5 Agam still lack entrepreneurial skills, as they tend to prioritize religiosity over practical skills. To address this issue, this study aims to integrate religious education with entrepreneurial skills through the studentpreneurship program, preparing students for the challenges of the Industrial Revolution 4.0. The objectives of this study are: (1) to explore the implementation of the studentpreneurship program at MAN 5 Agam, conducted annually, and (2) to assess the improvement of students' entrepreneurial character through this program in response to the Industrial Revolution 4.0. This research employs a qualitative method with a phenomenological approach and a case study design. Data were collected through in-depth observation and documentation analysis. The results indicate that the studentpreneurship program has been successfully implemented, leading to a positive impact on students, including the development of an entrepreneurial mindset through the creation of products such as satay, bread, and traditional pastries. These entrepreneurial skills not only contribute to students' personal development but also equip them with the competencies necessary to compete in the evolving job market of the Industrial Revolution 4.0.